Pengembangan Kemampuan Berpikir Kritis Anak Usia Dini melalui Pembelajaran Matematika Kontekstual - Majid, Abdul; Amir, Anggriani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Although studies that specifically examine the development of early childhood critical thinking skills through context-based mathematics learning remain limited, this ability plays an important role in supporting cognitive development and learning readiness at the next level. This study aims to test and analyze the effect of implementing contextual mathematics learning on early childhood critical thinking skills. This study employed a quantitative approach with a quasi-experimental design, involving 20 children in Group B at TK IGTKI-PGRI Harapan Bangsa Bonto Perak, Pangkep Regency, who were selected through a purposive sampling technique. The study was conducted from January to March 2026. Data were obtained through observation, critical thinking skills assessment sheets, and documentation of learning activities, and were then analyzed using descriptive statistics and a paired sample t-test. The results showed a significant improvement in children’s critical thinking skills after the implementation of contextual mathematics learning, with the mean score increasing from 55.30 at the initial stage to 82.15 at the final stage. The statistical test results showed a calculated t value of 9.27 with a significance value (Sig. 2-tailed) of 0.000, which was lower than 0.05, indicating that the treatment given had a significant effect. These findings confirm that learning that connects material with children’s real-life experiences is effective in encouraging the development of higher-order thinking skills. Thus, this study contributes to enriching the literature on context-based mathematics learning in early childhood education and provides practical implications for educators to design learning that is relevant to children’s everyday experiences.